Fostering cultural resilience: assessing the success of a locally engaged and adapted mental health intervention in Gaza - Rockowitz, Sarah; Bayoumi, Rasha; Parr, Nora; Awad, Abdullah; Altawil, Mohamed; Elmusharaf, Khalifa (Frontiers in Public Health, 2024)
In ongoing-conflict-affected regions like Gaza, the prevalence of complex and intersecting posttraumatic stress disorders (PTSDs) necessitates innovative interventions. Our study explores a mental health care approach that has been culturally adapted for fifteen years to address the complex landscape of PTSD in the Gaza Strip. Tarkiz was initially developed as 'Focusing', a metacognitive approach founded by Eugene Gendlin in 1950s Chicago. Tarkiz has been iteratively adapted and implemented for over a decade in Gaza by a team of local practitioners. The program's unique emphasis lies in its engagement approach, which relies on community participation and partnership building. The aim of this study was to qualitatively explore the perceived success of the program from the perspectives of the practitioners who adapted and delivered the program and the clients who participated in it. Data collection was driven by a multicultural research team, and prioritized capacity-building opportunities for Palestinian practitioners who lead on the development of research questions defining success. This exemplifies a successful science diplomacy model, emphasizing a collaborative approach, cultural sensitivity, and adaptable partnerships essential in global public health.